2018
DOI: 10.1111/trf.15028
|View full text |Cite
|
Sign up to set email alerts
|

Freezing of dendritic cells with trehalose as an additive in the conventional freezing medium results in improved recovery after cryopreservation

Abstract: BACKGROUND: Dendritic cell (DC) vaccination involves administration of multiple doses. Cryopreservation of tumor antigen-pulsed DCs can provide a ready to use vaccine source and eliminate the need of frequent withdrawal of the patient's blood for vaccine preparation. The aim of this study was to assess the effect of addition of trehalose in the freezing medium on the recovery of DCs after cryopreservation.STUDY DESIGN AND METHODS: DCs were generated from mononuclear cells from apheresis samples of healthy dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
8
0
2
Order By: Relevance
“…It remains unclear if the up-regulation of antioxidant genes after antioxidant treatment provides direct benefit, if any, to protect cells against cryopreservation-induced ROS damage. Trehalose [201,202] and BHT [203] were reported to reduce lipid peroxidation [204] in testicular tissue and spermatozoa, respectively, generally enhance total antioxidant capacity, improve cellular viability [204–207] and reduce apoptosis [205,207]. Decrease in mitochondrial membrane potential (Δψ) has been observed in cells stimulated by apoptotic stimulus [208–211], which is also seen in thawed cells after cryopreservation [65].…”
Section: Effectiveness Of Antioxidants In Preventing Cryoinjury: Lessmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains unclear if the up-regulation of antioxidant genes after antioxidant treatment provides direct benefit, if any, to protect cells against cryopreservation-induced ROS damage. Trehalose [201,202] and BHT [203] were reported to reduce lipid peroxidation [204] in testicular tissue and spermatozoa, respectively, generally enhance total antioxidant capacity, improve cellular viability [204–207] and reduce apoptosis [205,207]. Decrease in mitochondrial membrane potential (Δψ) has been observed in cells stimulated by apoptotic stimulus [208–211], which is also seen in thawed cells after cryopreservation [65].…”
Section: Effectiveness Of Antioxidants In Preventing Cryoinjury: Lessmentioning
confidence: 99%
“…Such impairments or undesirable outcomes of cellular functionality have been partly improved through administration of antioxidants. These include ascorbic acid [221], astragalosides [232], taurine [222], hypotaurine [178], vitamin E [76], catalase [221], trehalose [205–207], combination of catalase with trehalose [233,234] as well as combination of BHT with ascorbic acid [235] to cell types such as mononuclear cells, pancreatic islets, germ cells, spermatozoa, dendritic cells, hepatocytes and hemopoietic cells (Table 1). Among these antioxidants, winter wheat lipocalins and peroxiredoxins obtained from wheat are especially notable.…”
Section: Effectiveness Of Antioxidants In Preventing Cryoinjury: Lessmentioning
confidence: 99%
“…Trehalose is commonly used as a CPA. , Using it as the sole CPA could also protect cells and tissues even when it is not present in the cell. , …”
Section: Applications Of Trehalose In Cryopreservationmentioning
confidence: 99%
“…The most effective disaccharide antifreeze for exosomes is trehalose, which is mentioned as the best alternative ( Nakanishi et al, 2020 ). Trehalose and other membrane stabilisers have been used to store labile proteins, vaccines, liposomes, and cryopreserve tissues and stem cells, thus it makes sense to utilise them to keep exosomes stable ( Zhang X. G. et al, 2015 ; Bosch et al, 2016 ; Shinde et al, 2019 ). Budgude et al added 25 mM trehalose to exosomes in PBS at −80°C and found that these cryopreserved exosomes could be taken up by hematopoietic stem cells as efficiently as freshly isolated exosomes and that trehalose was as effective forfreshly isolated exosomes ( Budgude et al, 2021 ).…”
Section: Exosome Engineering Production and Preservationmentioning
confidence: 99%